1991
DOI: 10.3109/08941939109140778
|View full text |Cite
|
Sign up to set email alerts
|

Epithelialization and Blood Flow in Suction Blister Wounds on Healthy Volunteers

Abstract: Epithelialization and blood flow in painlessly inflicted small suction blister wounds were studied in healthy volunteers (n = 26) using evaporimetry and laser Doppler flowmetry (LDF), respectively. As expected, the evaporation rate normalized faster in wounds covered by an occlusive film than in wounds covered with gauze. The evaporimetry technique was found to be a simple alternative to the biopsy-based methods that have previously been used in humans. Blood flow was increased after 25 min of suctioning, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
1

Year Published

1991
1991
2005
2005

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 18 publications
0
23
1
Order By: Relevance
“…Arteries supplying the capillaries are larger and deeper in the skin and less likely to be occluded. A previous study found that prolonged application of vacuum increased blood perfusion, presumably because of the trauma of blistering (34); however, none of our conditions produced blistering.…”
Section: Discussioncontrasting
confidence: 65%
“…Arteries supplying the capillaries are larger and deeper in the skin and less likely to be occluded. A previous study found that prolonged application of vacuum increased blood perfusion, presumably because of the trauma of blistering (34); however, none of our conditions produced blistering.…”
Section: Discussioncontrasting
confidence: 65%
“…26,27 Studies of burn wounds suggest that wounds that heal rapidly without scarring have higher initial perfusion than those with slow healing. [28][29][30] Perhaps skin perfusion in diabetic patients may be insufficient to heal wounds without scarring. Even minor trauma may lead to scar formation in these patients.…”
Section: Commentmentioning
confidence: 99%
“…The LDI ratio refl ects blood perfusion in the erosion adjusted for that in adjacent skin. The subsiding hyperaemic reaction refl ected, to a certain degree, the prolonged hyperaemia observed in adults [19,26,27] . We do not know how nerve fi bres penetrate the epidermis in newborns, and the degree of neurogenous stimulation is thus unknown [28] .…”
Section: Discussionmentioning
confidence: 99%
“…Histologically this infl ammation is evaluated as mild [25] . Hyperaemia with an increase in microvascular permeability is sustained for days [19,26,27] . The LDI ratio refl ects blood perfusion in the erosion adjusted for that in adjacent skin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation